The Influence of Hard and Soft Information on Share Prices in LQ45 Index Companies Listed on the Indonesian Stock Exchange - Uciawati Uciawati; Robith Hudaya (Cita Konsultindo Research Center, 2023)
This research aims to determine the influence of earnings per Share (EPS), Price to Book Value (PBV), Sustainability Report Disclosure of Economic Dimensions, Environmental Dimensions, and Social Dimensions simultaneously and partially on stock prices. In this research, Sustainability Report disclosure is measured using the GRI Standard (2016). The population in this study are Liquid 45 Index (LQ45) companies listed on the Indonesia Stock Exchange in 2018-2022. This research uses a purposive sampling technique. Based on these sampling techniques and criteria, 15 companies were obtained with an observation period of five years, so the total observation was 75 samples. This research uses descriptive statistical analysis methods and panel data regression models using Eviews 12 software. Partial test results show that price-to-book value (PBV) has a significant positive effect on stock prices. In contrast, Earnings Per Share (EPS), Disclosure of Sustainability reports, Economic Dimensions, Environmental Dimensions, and Social Dimensions do not have a significant effect on stock prices. Simultaneously, Earnings Per Share (EPS), Price to Book Value (PBV), and Sustainability Report Disclosure of Economic Dimensions, Environmental Dimensions, and Social Dimensions have a significant effect on the share price of the LQ 45 Index listed on the Indonesia Stock Exchange for the 2018 - 2022 period.